PERAN PERBANKAN SYARIAH DALAM MELAKSANAKAN CORPORATE SOCIAL RESPONSIBILITY DI MASA COVID-19 - Amie Amelia; Nabilah Yusof (IAIN Batusangkar, 2020)
Islamic banks have an important role in social responsibility. As a part of Islamic Banking, Corporate social responsibility (CSR) has consequences on the welfare of the community, particularly, to those whose economic affected their economic by Pandemic Covid-19. CSR as a part of community empowerment provide aids like economic, social or health corresponding to theories of CSR. Ideally, CSR should have the value of truth, justice, kindness and honesty that can be manifested in business activities, especially Islamic banks and its relationships with all stakeholders. This research describes the role of Islamic banks in implementing corporate social responsibility during Pandemic Covid-19. Mandiri Syariah Bank as one Islamic Bank has couple of CSR programs such as Mitra Umat, Simpati Umat and Didik Umat. The results of this study also reveal Mandiri Syariah Bank has give aids; providing personal protective equipment (PPE) for medical personnel, helping the economy of the affected community, especially easing customer businesses during Pandemic Covid-19 as a form of social concern, as well as contributing to reducing poverty, company development, and economy and empowerment in accordance with the principles of CSR applied by Mandiri Syariah Bank like the principle of spirituality, nationalism and welfare.